(untitled) - Beierlein, James G. (Long Grove, Ill., 2008)
Through three successful editions, Principles of Agribusiness Management has provided a solid foundation for an entire generation of agribusiness students. The authors have refined and adapted each edition to the continually evolving world of agribusiness, and the comprehensive coverage in the fourth edition is no exception. New material on supply chains and leadership is incorporated throughout, and a new chapter has been added covering strategic planning and management. The authors maintain their classroom-tested approach, connecting each concept to their unifying theme that every manager's primary objective must be to maximize long-term profits by profitably satisfying customers' needs. Student learning is maximized with appealing, jargon-free language; clearly outlined learning objectives; a comprehensive glossary; and cases that apply the concepts in each chapter.
Keywords: Agricultural industries,Ngành nông nghiệp; Management,Quản lý